Leishmaniasis in Norway Rats in Sewers, Barcelona, Spain - Galán-Puchades, Maria Teresa (Emerg Infect Dis, 2019)
We detected Leishmania infantum in 98 Norway rats (Rattus norvegicus) trapped in parks and sewers of Barcelona, Spain. The 84 rats from the sewers showed a prevalence of 33.3% and up to 2,272 estimated parasites. These results, in the most abundant potential reservoir in cities, is of public health concern.